Abundance and Characteristics of Microplastic in the Selected Coastal Area of Pangasugan, Baybay City, Leyte, Philippines - Abu Sayed Al Helal; Abu Bakar Siddique; Masum Howlader; Micaela Dador; Victor Asio (Recoletos Multidisciplinary Research Journal, 2025)
Background: Microplastics (MPs) less than 5 mm in size were detected in marine water, which is promoting growing research interest beyond the marine environment into soil, freshwater, and drinking water. This study investigated the presence and characteristics of MPs in water samples from Visayas State University beach, Pangasugan, Leyte. Methods: Samples (n=20) were collected from 20 sites based on spatial variation. MPs were isolated via density extraction and filtration, identified under a microscope, and analyzed chemically using FTIR. Results: The average contamination level was 132.5 items/L. MPs were categorized by shape, color, size, and polymer type, with fibers (62%) being most prevalent, followed by fragments and pellets (9.4%). Black (24.5%) was the most common color. Identified polymers included ABS (acrylonitrile butadiene styrene), EVA (ethylene vinyl acetate), PA (polyamide), and PET (polyethylene terephthalate). Conclusion: Given the direct exposure of aquatic ecosystems to this contamination, further studies are recommended to assess health risks, offering crucial baseline data for future research.